Reformulation of Criminal Sanctions For Perpetrators And Legal Protection For Victims of Sexual Harassment - Anthony Rahardjo; Binsar Jon Vic (al-Battar: Jurnal Pamungkas Hukum, 2025)
Sexual harassment remains a persistent and systemic problem in Indonesia, reflecting ongoing weaknesses in criminal regulation, law enforcement practices, and victim-oriented protection mechanisms. Although legal frameworks such as the Indonesian Criminal Code (Law No. 1 of 2023) and the Law on the Crime of Sexual Violence (Law No. 12 of 2022) have been enacted to address sexual violence, their implementation has not yet produced a sufficient deterrent effect for perpetrators nor comprehensive legal and psychosocial protection for victims. This study aims to critically examine the adequacy of existing criminal sanctions against perpetrators of sexual harassment and to formulate a more effective model of legal protection for victims based on principles of justice and victim recovery. The research is grounded in normative legal research employing a statutory and conceptual approach, with primary legal materials consisting of relevant legislation and secondary materials derived from legal doctrines, scholarly literature, and previous studies. The underlying hypothesis of this study is that current criminal sanctions and victim protection mechanisms are inadequate to address the complex impacts of sexual harassment and therefore require substantive reform. The findings indicate that the relatively light criminal penalties, evidentiary difficulties, and the persistence of victim-blaming practices undermine effective law enforcement and victim recovery. Accordingly, this study emphasizes the urgency of reformulating criminal sanctions to enhance their deterrent effect, strengthening victim-centered legal protection, improving access to legal aid and psychosocial rehabilitation, and refining evidentiary standards in judicial proceedings to ensure a more just, responsive, and comprehensive legal framework for addressing sexual harassment in Indonesia.